Sleep Quality Monitoring and Notification System for Homecare Patient - Ahmat Alim, Mohamad Zain; Nor'aisah Sudin (Evolution in Electrical and Electronic Engineering, 2021)
Human physical and mental health, as well as daytime performance and safety, are all influenced by sleep quality. Good sleep can lower the risk of chronic disease. An improved sleep quality monitoring system is required to assist patients in getting better sleep. By leveraging the rapid improvement of sensor and mobile technologies, the emergence of internet-of-things technology has created a potential chance to build a reliable sleep quality monitoring system. Health monitoring and condition evaluation should be carried out as soon as possible so that better clinical choices may be made about a patient’s state in terms of heartbeat and temperature at home. Healthcare interaction via the Internet of Things (IoT) is implemented in order to access home care patient medical criteria at home. This health monitoring station, created using Blynk Applications, focuses on giving reliable data as well as information and early warnings regarding health issues for homecare patients. The evaluation and monitoring activities are aimed to monitor the patient’s current condition so that the health system can be controlled and effective steps may be taken based on these observations. Normal and abnormal situations can determine the patient’s heart rate in most cases. It is considered normal if the pulse rate is between 35 and 89 beats per minute. If the value is below 35 or above 90, the effect is the opposite. The system uses an alarm to inform the caregiver. When the microcontroller receives data from sensors and detects abnormal activities, the buzzer will turn on. The goal of the buzzer alert is to notify and alert the caregiver that immediate action is required. As a result, this approach can be extremely helpful in preventing patients from becoming critically ill while they are sleeping or awake, as well as raising caregiver awareness.